Targeting mechanisms of tailed bacteriophages - Nobrega, Franklin L; Vlot, Marnix; de Jonge, Patrick A; Dreesens, Lisa L; Beaumont, Hubertus J E; Lavigne, Rob; Dutilh, Bas E; Brouns, Stan J J (Nature reviews. Microbiology, 2018)
Phages differ substantially in the bacterial hosts that they infect. Their host range is determined by the specific structures that they use to target bacterial cells. Tailed phages use a broad range of receptor-binding proteins, such as tail fibres, tail spikes and the central tail spike, to target their cognate bacterial cell surface receptors. Recent technical advances and new structure-function insights have begun to unravel the molecular mechanisms and temporal dynamics that govern these interactions. Here, we review the current understanding of the targeting machinery and mechanisms of tailed phages. These new insights and approaches pave the way for the application of phages in medicine and biotechnology and enable deeper understanding of their ecology and evolution.